Derivative and Lipschitz Type Characterizations of Variable Exponent Bergman Spaces - Rumeng Ma; Jingshi Xu (Journal of Function Spaces)
We give derivative and Lipschitz type characterizations of Bergman spaces with log-Hölder continuous variable exponent.